Cytokines and apoptosis in atopic dermatitis - Szymański, Łukasz; Cios, Aleksandra; Ciepielak, Martyna; Stankiewicz, Wanda (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Atopic dermatitis (AD) is the most common chronic inflammatory skin disease. AD affects 10–20% of children worldwide and persists into adulthood in a minority of cases, affecting approximately 2–3% of the adult population, with an increased prevalence over the past decades in developed countries. Atopy is a genetic tendency to overproduce IgE class antibodies in response to common antigens found in the environment. Concurrence of different atopy such as allergic rhinitis or asthma in children with AD is estimated at 80%. AD is characterized by a vicious cycle of an allergic immune response. The emerging picture of the AD is a complex disorder with barrier dysfunction, immunological, genetic and environmental factors all playing key roles. Patients with severe or persistent disease and their families experience significant impairment in their quality of life, and in addition, AD places a heavy economic burden on society as a whole. Pathogenesis, the role of the epidermal barrier, mechanisms of cells apoptosis, the role of T cells and cytokines in AD are discussed in this article.